Vitamin D Deficiency among Children with Sepsis in a Tertiary Care Center in Eastern Nepal - Kafle, Shyam Prasad; Ahmad, Eqtedar; Rauniyar, Lalan Prasad; Koirala, Namu (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION: Vitamin D deficiency (VDD) is exceedingly predominant in children leading to dysregulation of the immune system and inflammation. Data on the prevalence of VDD in children with sepsis and its association with sepsis severity are limited from our part of the world. The primary aim of this study was to identify the burden of VDD in children with sepsis. MATERIAL AND METHODS: One hundred and five children (< 15 years) with sepsis were enrolled from April 15, 2017 to April 14, 2018 from a tertiary care center in Eastern Nepal. Demographic data including BMI, sequential organ failure assessment (SOFA) scores were recorded at the time of admission. Plasma 25-hydroxy vitamin D [25(OH)D] levels were measured by chemiluminescence immunoassay technique (CLIA) (MAGLUMI 25-OH Vitamin D; CLIA) within 24 hours of admission. Vitamin D concentrations of <20 ng/mL (50 nmol/L) were considered as deficient. RESULTS: Of the 105 children enrolled, the majority 74 (70.55%) had vitamin D deficiency. Vitamin D was deficient in 77, 65, and 66% of children in 1-5, 5-10, and 10-15 years of age group respectively. Vitamin D deficiency was maximum (80%) in underweight children. In the VDD group, 60% had severe sepsis, whereas only 32% had severe sepsis in vitamin D sufficient group with significant statistical association with sepsis severity and vitamin D deficiency. CONCLUSION: A high burden of VDD is present in children with sepsis which was found to be associated with greater severity of illness.